1996
DOI: 10.1046/j.1365-2788.1996.768768.x
|View full text |Cite
|
Sign up to set email alerts
|

Population prevalence of psychopathology in children and adolescents with intellectual disability: II epidemiological findings

Abstract: This paper reports findings from an epidemiologically derived population in a multicentre study in NSW, Australia. The design of this study is described in the accompanying paper. Those with mild intellectual disability (ID) were likely to have been underascertained, but identification and participation rates for those with more severe ID were high. The study found that in the regions surveyed 40.7% of those with ID and aged between 4 and 18 could be classified as having severe emotional and behaviour disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
191
2
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(216 citation statements)
references
References 21 publications
17
191
2
6
Order By: Relevance
“…The DD group provided a very stringent comparison group, with nearly 90% of the children meeting criteria for a language disorder, cognitive impairment, or another developmental disability. These children demonstrate many behaviors resembling those of ASDs (Einfeld and Tonge 1996;Bishop and Norbury 2002).…”
Section: Limitations and Future Directionsmentioning
confidence: 96%
“…The DD group provided a very stringent comparison group, with nearly 90% of the children meeting criteria for a language disorder, cognitive impairment, or another developmental disability. These children demonstrate many behaviors resembling those of ASDs (Einfeld and Tonge 1996;Bishop and Norbury 2002).…”
Section: Limitations and Future Directionsmentioning
confidence: 96%
“…The DBC-P also provides a cluster of seven symptoms of Attention Deficit Hyperactivity (DBC-ADH) (Kenway, 1994; as well as a Depression Scale (DBC-D) which records 10 DSM-IV behavioural signs of depression . The DBC-P has been used in a broad range of research including the nature of psychiatric disorder in children with intellectual disability (Tonge et al, 1996); epidemiological studies, (Einfeld & Tonge, 1996b;Cormack, Brown, & Hastings, 2000;Dekker, Nunn, Einfeld, Tonge, & Koot, 2002;Koskentausta & Almqvist, 2004); behavioural phenotypes (Einfeld, Tonge, & Florio, 1997;Einfeld, Smith, Durvasula, Florio, & Tonge, 1999;Einfeld, Tonge, & Rees, 2001) and psychopathology in children with ID and its impact upon parental wellbeing (Hoare, Harris, Jackson, & Kerley, 1998). The DBC-P has been used to develop a screen for autism, the Developmental Behaviour Checklist Autism Screening Algorithm, (DBC-ASA) (Brereton, Tonge, Mackinnon, & Einfeld, 2002;Steinhausen & Metzke, 2004) and to differentiate the .5 0 behavioural profile in autism and mental retardation (Steinhausen & Metzke, 2004).…”
Section: Psychopathologymentioning
confidence: 99%
“…Depression has been examined in individuals with varying levels of intellectual disability (Benson & Ivins, 1992;Einfeld & Tonge, 1996;Glenn, Bihm, & Lammers, 2003;Luftig, 1988;Reiss & Rojahn, 1993). Studies have revealed that individuals with mild intellectual disability report lower self-perceptions and more depression than those with severe intellectual disability (Benson & Ivins, 1992;Reiss & Rojahn, 1993).…”
Section: Self-perceived Social Competence and Depression In Hfasdmentioning
confidence: 99%